Understanding the Critical Role of the Ag Nanophase in Boosting the Initial Reversibility of Transition Metal Oxide Anodes for Lithium-Ion Batteries - Lee, Daehee; Wu, Mihye; Kim, Dong-Hyun; Chae, Changju; Cho, Min Kyung; Kim, Ji-Young; Lee, Sun Sook; Choi, Sungho; Choi, Youngmin; Shin, Tae Joo; Chung, Kyung Yoon; Jeong, Sunho; et al. (American Chemical Society, 2017)
The initial reversible capacity, a critical impediment in transition metal oxide-based anodes, is augmented in conversion-reaction-involved CoO anodes for lithium-ion batteries, by incorporating a chemically synthesized Ag nanophase. With an increase in the added amount of Ag nanophase from 5 to 15 wt %, the initial capacity loss decreases linearly up to 31.7%. The Ag nanophase maintains its pristine metallic nature without undergoing phase transformations, even during repeated vigorous electrochemical reactions of the active CoO phase. Complementary ex situ chemical/physical analyses suggest that the Ag nanophase promotes the catalytic generation of reversible gel-like/polymeric films wherein lithium ions are stored capacitively in the low-voltage region below 0.7 V during discharging. These scientific findings would provide a heretofore unrecognized pathway to resolving a major issue associated with the critical irreversibility in conversion-type transition metal oxide anodes.
Keywords: ELECTRODE MATERIALS; CAPACITY; REACTIVITY; NANOPARTICLES; ORIGIN; LAYER; COO